Topographic and Mechanical properties of the Compound (Ni-Al2O3-TiO2) Prepared by using Method. (Journal of the College of Basic Education, 2022)
Where the current research included the manufacture of models using the method of powders, where samples were prepared from taking nickel as a base material and alumina at a constant rate (10%), while titanium oxide (TiO2) was in percentages of (0,5,10,15,20)% and the powders were ground and mixed using a grinder. Homemade steel balls contained for one hour after which the samples were pressed at a pressure of 5 Ton for one minute. The prepared samples appeared at a temperature of 1300 °C and for a time only 2 hours. The SEM examination was performed as well as the physical examinations (hardness, radial compressive strength, wear), all before and after sintering. The results of the scanning electron microscope showed a clear microstructure and the best uniformity and crystal cohesion for it at the ratio 15% TiO2 As for the hardness only it gave the best hardness for Vickers at the ratio 15% TiO2 and reached 170.82Hv, while the diagonal compression resistance was the best value for it at the same The ratio also reached 49.5 MPa, while the wear values ​​decreased with increasing the concentration to reach the lowest when (20N) and at 15% TiO2.